Analisis Fakor Internal dan Eksternal yang Memengaruhi Financial Distress Bank Umum Syariah Periode 2014-2018 - Dhiwi Rasa Wulan Pamungkas; Fatmi Hadiani; Radia Purbayati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The purpose of this study is to determine the influence of Non Performing Finance (NPF), Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Inflation, and Gross Domestic Product (GDP) on Financial Distress as measured by Grover method (G-Score). The sample of this study used a purposive sampling method and obtained 12 Islamic Commercial Banks in Indonesia to be analyzed. The data in this study were sourced from annual report Islamic Banks and reports on inflation and Gross Domestic Product (GDP). This research will be analyzed by a logistic regression model that will be tested using the EViews version 10 SV software. The results of this study indicate that there are four Islamic Commercial Banks in Indonesia that experienced financial distress during the 2014-2018 period. Partially, NPF and inflation have a significant effect on financial distress, while FDR, CAR, and GDP have no significant effect on financial distress.